PENGEMBANGAN KUALIFIKASI PEMIMPIN PENDIDIKAN NONFORMAL DAN INFORMAL DITINJAU DARI PERSPEKTIF DHOFIER DAN MUHAIMIN - Arief Dwi Kurniawan; Suwito (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the development of qualifications of non-formal and informal education leaders through the theoretical perspective of Zamaksyari Dhofier and Muhaimin Endang. The focus of the study is directed at the integration of spiritual, managerial, and technological adaptation dimensions as the foundation of holistic leadership in facing social, cultural, and educational digitalization dynamics. The method used is a literature study with descriptive analysis of national education regulations, academic works, and previous research. The results of the study show that according to Dhofier, non-formal and informal education leadership requires spiritual integrity, moral charisma, and participatory leadership based on local values. Meanwhile, Muhaimin emphasized the importance of managerial competence, resource efficiency, inclusive vision, and sustainable self-development. The synthesis of these two perspectives results in a leadership model that balances spirituality with professionalism, as well as being responsive to the challenges of the digital age. The main obstacles in the form of limited formal training, lack of infrastructure, and cultural resistance can be overcome through community-based training programs, the use of digital technology, and the strengthening of cross-agency collaboration. This research confirms that non-formal and informal education leaders must have multidimensional qualifications that are able to inspire, empower, and build an inclusive, adaptive, and sustainable learning society, thereby supporting the goals of national education and lifelong learning in the era of globalization.